Credo in unam credentiam: religious beliefs are standard beliefs. - Ryan, Liam D. (Synthese, 2024)
Does religious belief differ in any interesting way from other kinds of belief? For now, take ‘belief' to mean how one takes the world to be, on the basis of which they act. Call beliefs like this ‘ordinary beliefs'. There are also more complicated, or abstract, beliefs. Call such beliefs ‘non-ordinary beliefs’. Are religious beliefs different in any significant or interesting way from what we call ‘standard belief’? Our analysis shows that they are not. Although the content of religious belief is different, and sometimes so is the function, religious beliefs are still mental, dispositional attitudes that aim to provide a correct representation of the world. Therefore, religious beliefs are best understood as a sub-category of standard beliefs, alongside ordinary and non-ordinary beliefs. This account of religious belief provides further insight into the meaning of belief and supports a revision of a strict demarcation between standard and non-standard beliefs.